Statistical Physics for Biological Matter - Sung, Wokyung (Graduate Texts in Physics,, 2018)
This textbook covers a broad range of topics in statistical physics, including statistical mechanics (equilibrium and non-equilibrium), soft matter and fluid physics, for applications to biological phenomena at both cellular and macromolecular levels. Typical statistical physics courses cover ideal gases (classical and quantum) and interacting units of simple structures. In contrast, even simple biological fluids are solutions of macromolecules, the structures of which are very complex. This book fills this wide gap by providing appropriate content as well as by explaining the theoretical method that typifies good modeling, namely, the method of coarse-grained descriptions that extract the most salient features emerging at mesoscopic scales. The major topics covered in this book include thermodynamics, equilibrium statistical mechanics, soft matter physics of polymers and membranes, non-equilibrium statistical physics covering stochastic processes, transport phenomena and hydrodynamics. Generic methods and theories are described with detailed derivations, followed by applications and examples in biology. By systematically and coherently covering the basic principles, this book helps the readers to build up their understanding of nonspecific concepts and theoretical methods, which they may be able to apply to a broader class of biological problems. While intended as a graduate level textbook, it can also address the interested senior level undergraduate. In addition, it is suitable for those involved in research on biological systems or soft matter based on physics, particularly on statistical physics.